Pemberdayaan Ekonomi Masyarakat Melalui Home Industry - Puji Maya Sari; Indira Sabeth Rahmawaty (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2020)
This study aims to analyze the community economic empowerment program through the implementation program and the results of community economic empowerment through the tulangsapi craft home industry in Pasirtukul Village. This research method is a qualitative research using descriptive method. Data collection techniques used, interviews, and documentation. Data analysis was carried out through a logical interpretation that spread with the context of Community Economic Empowerment. The results of the study showed that the Community Economic Empowerment program through the home of Cattle Bone craft industry was an activity used to provide information. Build with manufacturers for craftsmen with the aim of improving the economy of the craftsmen. In addition, from this activity the community is given craft tools and procedures for managing production results. The process carried out by agricultural training consists of several stages, namely the pre-implementation stage, the manufacturing process, the process and the discussion. the community is clearer in managing handicrafts; the craftsman community finds more in the home industry; The economic control of the community through industrial houses, cow bone crafts, produces relations and network links for craftsmen to improve their handicrafts